TI_GERICHTE 12.2017.128 vom 12. Juli 2019 , Appalto - mercede - lavori a regia - garanzia per difetti - norma SIA 118 - TI Tribunale d'appello (2019)
Appalto - mercede - lavori a regia - garanzia per difetti - norma SIA 118